LESSONS FROM THE BOER WAR - De Jong, C. (Scientia Militaria - South African Journal of Military Studies, 2012)
Review of: Jay Stone and Erwin A. Schmidl, The Boer War and Military reforms, Volume 28 of the series "War and Society of East Central Europe", University Press of America, Lanham: New York - London, 1988, 345 pp. Numerous studies exist of the lessons to be learnt from the Anglo-Boer War 1899-1902 by students of 20th Century Warfare. These studies date back from the days of that war up to the present. In many cases these studies are titled "Lessons from the Boer War". In the book under review Jay Stone examines the War’s impact on Britain and Erwin Schmidl its effect in Austria-Hungary. I shall confine this review to Stone’s findings. According to him Britain entered the war full of self-confidence in the hope of terminating the conflict within a few weeks, but was totally unprepared. The reason was that the last war she waged against a European power was as long ago as 1855-56. That was the Crimean War against Russia. Thereafter she had fought only local, colonial wars against badly drilled, little disciplined and primitively armed non-European armies. Some of these used to attack in large hordes and were shot or ridden down en masse. This had happened recently at Omdurman in 1898 where Kitchener defeated the Sudanese. The British ultimately were victorious in all the colonial wars.